Original Report: “All inside vs Antero medial portal anterior cruciate ligament reconstruction technique: which is better?” - Lalit Mohan Gupta; Vivek Vivek; Amresh Ghai; Munish Sood; Shalendra Singh; Vikas Dhawan (Journal of Orthopedics, Traumatology and Rehabilitation)
Objective: Anterior cruciate ligament (ACL) tears are common injuries and have long-term effects on sportspersons and high-demand professionals like military personnel. The goal of ACL reconstruction surgery is to get back the individual to the preinjury status which may not always be possible. The study aimed to assess outcomes using two techniques of ACL reconstruction. Materials and Methods: Fifty patients with an isolated ACL injury and meeting the inclusion were operated on and evaluated at our center using all-inside and anteromedial ACL reconstruction techniques. Twenty-five patients were operated using each technique. The groups were compared in terms of operative issues and postoperative complications, in addition to functional outcome scores and Tegner’s return to injury level. Results: The average age of patients was more than 30 years. All were male patients. Sports injuries were the most common mode of injury in both groups constituting more than 60% of all the injuries. The median Tegner, mean Lysholm score, and mean 2000 International Knee Documentation Committee subjective knee score were comparable preoperatively, and the scores improved in both the groups at the final follow-up of 2 years. However, the difference in the score between the two groups was not statistically significant. Conclusions: Despite the learning curve, the all-inside ACL reconstruction technique yields outcomes similar to the AM portal technique in terms of functional outcome and return to the preinjury level at mid-term follow-up.